О влиянии параметров внутренней баллистики на живучесть танкового вооружения - Анипко, О. Б.; Бирюков, И. Ю.; Бусяк, Ю. М.; Канищев, С. П.; Переход, А. Н. (НТУ "ХПИ", 2008)
The article presents the factors affecting the tank armament survivability and finds relation between the maximum pressure and the initial velocity for rounds with the shelf life more than guaranteed.
Keywords: ствольная система; разгар ствола; механический износ; омеднение